Cathode Materials: Atomic Insights into the Enhanced Surface Stability in High Voltage Cathode Materials by Ultrathin Coating (Adv. Funct. Mater. 7/2017). (February 2017) - Fang, Xin; Lin, Feng; Nordlund, Dennis; Mecklenburg, Matthew; Ge, Mingyuan; Rong, Jiepeng; Zhang, Anyi; Shen, Chenfei; Liu, Yihang; Cao, Yu; Doeff, Marca M.; Zhou, Chongwu
Abstract : Atomic layer deposition of Al2 O3 is employed as ultrathin coating on LiNi0.5 Mn1.5 O4, a high voltage cathode in Li‐ion batteries. X‐ray absorption spectroscopy and scanning transmission electron microscopy electron energy loss spectroscopy show that the coating suppresses Mn 2+ formation on the surface and decelerates impedance buildup. The detailed analysis by Chongwu Zhou and co‐workers is shown in article number 1602873.